2014
DOI: 10.1590/0001-3765201420140173
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro effects of fructose on rat brain acetylcholinesterase activity: an ontogenetic study

Abstract: Increased fructose concentrations are the biochemical hallmark of fructosemia, a group of inherited disorders on the metabolic pathway of this sugar. The main clinical findings observed in patients affected by fructosemia include neurological abnormalities with developmental delay, whose pathophysiology is still undefined. In the present work we investigated the in vitro and in vivo effects of fructose on acetylcholinesterase (AchE) activity in brain structures of developing rats. For the in vitro experiments,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Their findings suggested an acceleration in neurodegeneration and in Aβ plaque formation after HFD-induced acute inflammation and NAFLD development [30]. The fact that HFD and fructose-rich diets may quicken AD cognitive decline has also been confirmed in recent experimental studies [32][33][34].…”
Section: Neurodegenerative Diseases: Alzheimer's Diseasementioning
confidence: 82%
See 1 more Smart Citation
“…Their findings suggested an acceleration in neurodegeneration and in Aβ plaque formation after HFD-induced acute inflammation and NAFLD development [30]. The fact that HFD and fructose-rich diets may quicken AD cognitive decline has also been confirmed in recent experimental studies [32][33][34].…”
Section: Neurodegenerative Diseases: Alzheimer's Diseasementioning
confidence: 82%
“…Moreover, an excessive consumption of fructose, a monosaccharide mainly used as sweetening agent in soft drinks, in addition to systemic metabolic alterations, was able to induce oxidative stress, thereby causing lipid peroxidation and protein nitrosylation in the hippocampus and reducing the expression of synaptic proteins, leading to impaired synaptic function, thus affecting learning and memory in a long-lived animal model [ 48 ]. Accordingly, many reports investigating the association between obesity and cognitive impairment have reported that the consumption of high-fat and high-sugar diet is able to increase oxidative stress, inflammation, and AChE activity, leading to cerebrovascular changes and neuronal loss in the hippocampus, disrupt myelination and axonal transmission, and decrease of dopamine (DA) and serotonin (5-HT) in the hippocampus, two of the key neurotransmitters involved in learning and memory processes [ 33 , 34 , 49 , 50 ].…”
Section: Molecular and Pathophysiological Pathways Connecting Naflmentioning
confidence: 99%